Glaubenskrisen, Neue Religionen und der Papst: Religion in »Stern« und »Spiegel« von 1960 bis 2014 - Stander-Dulisch, Judith, (transcript, 2018)
New religions, the Pope, spirituality, ecclesiastical controversies: This study explores how the news magazines Stern and Spiegel treat the subject of religion.